2005
DOI: 10.1300/j064v25n02_08
|View full text |Cite
|
Sign up to set email alerts
|

Growing and Selling Pasture-Finished Beef: Results of a Nationwide Survey

Abstract: This paper reports the results of a broad survey of 149 producers who identify their product as "pasture-finished" beef. Returns are from 46 different US states and Canada. Survey responses provide information on farm background characteristics, production systems, and marketing. Results show consensus on many points, and diversity on many others. The structure of the pasture-finished beef enterprise is built on direct marketing, niche marketing, source identification, value added, and rising consumer consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…In order to manage these contrasting attributes and to inform government policy (Asgedom and Kebreab 2011), it is important to document the current husbandry practices used in beef cattle operations and to document changes that have occurred over time. The last targeted, extensive farm survey of beef cattle husbandry in Canada, the Livestock Farm Practices Survey (LFPS), was completed in 2006 (Sheppard et al 2009;Sheppard and Bittman 2012), with a more limited survey of the sale and consumption of pasture-finished beef being conducted in 2005 (Lozier et al 2005). The LFPS was conducted at an important juncture in the industry as a consequence of the lingering trade restrictions related to the identification of bovine spongiform encephalopathy in Canadian cattle in 2003, which disrupted the export of Canadian beef.…”
Section: Mots Clé Smentioning
confidence: 99%
See 1 more Smart Citation
“…In order to manage these contrasting attributes and to inform government policy (Asgedom and Kebreab 2011), it is important to document the current husbandry practices used in beef cattle operations and to document changes that have occurred over time. The last targeted, extensive farm survey of beef cattle husbandry in Canada, the Livestock Farm Practices Survey (LFPS), was completed in 2006 (Sheppard et al 2009;Sheppard and Bittman 2012), with a more limited survey of the sale and consumption of pasture-finished beef being conducted in 2005 (Lozier et al 2005). The LFPS was conducted at an important juncture in the industry as a consequence of the lingering trade restrictions related to the identification of bovine spongiform encephalopathy in Canadian cattle in 2003, which disrupted the export of Canadian beef.…”
Section: Mots Clé Smentioning
confidence: 99%
“…However, because of the increased land use associated with pasture finishing, this too may be criticized. Lozier et al (2005) and Perillat et al (2004) reported on the risks and benefits of finishing beef on pasture.…”
Section: Warm Season Grazingmentioning
confidence: 99%
“…A price sensitivity analysis could also indicate the economic feasibility of increased production levels and the need to consider new markets (other than hay) for alfalfa and other forages as production increases. One possibility could be the expansion of pasture-based livestock systems, demanded by a growing consumer sector 89 and offering many ecological services as compared to decoupled row crop and livestock systems 90 91 . Although alfalfa (and most other crop) prices have risen along with corn, the high corn prices of 2006 made corn, on average, more profitable than alfalfa.…”
Section: Som 148% Greater Som With C-s-o/a-a-a Than C-s-c-s-c 26 Soilmentioning
confidence: 99%
“…Two surveys targeted only grass-based beef producers and focused on their production and marketing practices (Lozier et al 2005;Steinberg andComerford 2009). Evans et al (2007) used stochastic simulations to compare productions systems in the Appalachian cow-calf sector.…”
Section: Grass-based Productionmentioning
confidence: 99%